The Impact of Gross Regional Domestic Product (GRDP) in The Processing, Construction, Transportation and Warehousing, Information and Communication Sectors on The Environmental Quality Index (A Case Study of 34 Provinces in Indonesia) - Ramadhani, Yoga Ilham; Aisyah, Siti (Universitas Muhammadiyah Surakarta, 2024)
The rate of economic growth is the primary metric used to evaluate the effectiveness of economic development, reflected in a prosperous society. This study aims to determine the impact of economic contribution in the processing, construction, transportation and warehousing, and the information and communication (ICT) sector to the Environmental Quality Index (EQI) in Indonesia. The method used is panel data regression utilizing the cross-sectional data of 34 provinces 2018 to 2022. The data was obtained from Statistics Indonesia and the Ministry of Environment and Forestry (EQI). The findings indicate that the GRDP of the construction and ICT sectors has a positive and significant effect on the EQI, while the GRDP of the transportation and warehousing sectors negatively impacts the index, whereas the processing sector has no significant impact. This shows that economic development in these sectors affects the environmental quality, both positively and negatively, depending on the sector in question. Further recommendations include the need for sustainable development policies especially related to the development of green ICT can help to balance economic growth with environmental preservation.